Teacher’s Perspectives on the Representation of Children with Special Educational Needs in Irish-Medium Contexts - Fitzgerald Spollen, Sarah (Marino Institute of Education, 2021)
This research study explores teacher’s perspectives on the level of representation of children with special educational needs (SEN) in Irish-medium schools. In recent years, there has been a significant rise in demand for Irish-medium education. (Gaeloideachas, 2020). An Chomhairle um Oideachas Gaeltachta agus Gaelscolaíochta (COGG) reported that there were 50,000+ children and young people enrolled in Irish-medium education in 2010. According to Gaeloideachas.ie (2020), the percentage of pupils attending Gaelscoileanna in the Republic of Ireland reached a record level in the academic year 2018/2019. In the context of these statistics, the researcher posed the following question: if there are 50,000+ children being educated through the medium of Irish, what is the level of representation of children with SEN within this figure? This research study investigates, through the eyes of primary Irishmedium teachers, the level to which children with SEN are represented in Gaelscoileanna. Are they under-represented, equally represented, or over-represented? Additionally, this study questions what the level of representation means for the pupils, the teachers, the school, and the parents of children with SEN. A qualitative approach was taken for this research in which eight primary Irish-medium teachers were interviewed. The interviews were semi-structured and were conducted through the language of instruction in the school, Gaeilge. This approach allowed the researcher to gain a deeper understanding and insight into the experiences and perspectives of teachers regarding the level of representation of children with SEN in an Irish-medium school. The need for research in this area grows as the demand for Irish-medium education increases, respectively. In reviewing the relevant literature pertinent to this area, the researcher found that there were some contrasting viewpoints in relation to the suitability of Irish-medium iv education for children with SEN. These contrasting viewpoints stand as rationale for the researcher to conduct further research in this area. The researcher believes that these contrasting viewpoints play a fundamental role in the influence on the current level of representation of children with SEN in Gaelscoileanna. The findings in Chapter Four echo the contrasting viewpoints discussed in review of literature as many of the participants held similar views. These findings have helped the researcher gain an insight into the level of representation of children with SEN in Irish-medium schools.
Keywords: Special educational needs (SEN).; Irish- medium; Gaelscolaíocht (COGG); Irish medium teachers; Ireland; Education; Irish-language schools; Children with disabilities; Teachers